The impact of shear wall location on the seismic response of RC frame buildings resting on sloping ground - Acharya, Upama; Shrestha, Jagat Kumar (Journal of Innovations in Engineering Education, 2019)
It is observed during the past earthquakes, buildings in hilly regions have experienced high degree of damage leading to collapse though they have been designed for safety of the occupants against natural hazards. Hence, while adopting practice of multistory buildings in these hilly and seismically active areas, utmost care should be taken for making these buildings earthquake resistant. For the buildings on sloping ground, the height of columns below plinth level is not same which affects the performance of building during earthquake. Hence to improve the seismic performance of building shear walls play very important role.It is very necessary to determine the most effective location of shear walls. Shear wall arrangement must be accurate, because if not, it will cause negative effect instead. This paper is aimed at predicting the effect of positioning RC shear wall of different shape on the structural response of RC building resting on sloping ground. Eight models have been prepared considering earth pressure and without considering earth pressure. The displacement of building is to be determined by nonlinear static pushover analysis. For the purpose of pushover analysis and response spectrum analysis finite element-based software SAP 2000 has been utilized.